2011
DOI: 10.1590/s1516-89132011000100002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of picloram, additives and plant growth regulators on somatic embryogenesis of Phyla nodiflora (L.) Greene

Abstract: The present study describes the plant regeneration via somatic embryogenesis in suspension culture derived from the leaf and stem explants of Phyla nodiflora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In addition, it was observed that IAA and IBA drastically reduced the callus biomass resulting in WFC natured calli all the media. These results are well authenticated with the previous reports of Ahmed et al (2011), who demonstrated that NAA and 2,4-D were suitable in the callus induction of P. nodiflora. P. nodiflora callus growth curve was sigmoid type and four growth phases can be distinguished in different days (15, 25, 35, 45 and 55 days).…”
Section: Callus Induction and Growth Curve Analysissupporting
confidence: 91%
“…In addition, it was observed that IAA and IBA drastically reduced the callus biomass resulting in WFC natured calli all the media. These results are well authenticated with the previous reports of Ahmed et al (2011), who demonstrated that NAA and 2,4-D were suitable in the callus induction of P. nodiflora. P. nodiflora callus growth curve was sigmoid type and four growth phases can be distinguished in different days (15, 25, 35, 45 and 55 days).…”
Section: Callus Induction and Growth Curve Analysissupporting
confidence: 91%
“…Figure 4 also showed that picloram-derived cultures had the lowest similarity (0.34). Picloram is an auxinic herbicide belong to the pyridine group and commonly used at low concentration as an inducer for callus formation during somatic embryogenesis regeneration (Firoozabady & Moy 2004;Ahmed et al et al 2011;Noormi 2012). Beside regenerated through callus formation phase, it needs a longer time to conduct somatic embryogenesis, so that the probability of genetic changes would increase.…”
Section: Regeneration Methods Affects the Somaclonal Variation Of Pinementioning
confidence: 99%
“…Plants also produce certain chemicals to overcome abiotic stresses. In this aspects plant tissue culture developed callus influenced by medium, explants, plant growth regulators, color lights, temperature, photoperiod and carbon sources are helpful to produce valuable secondary metabolites compounds in many studies [3,4]. Growing a plant outside its natural environment under ideal conditions may therefore, result in being unable to produce the desired bioactive substances, hence the need for prior evaluation.…”
Section: Application Areamentioning
confidence: 99%
“…Environmental factors on the other hand are the culture conditions under which explants are maintained. The environmental factors involved include the temperature and illumination of the culture room, agitation process and incubation period of the cultures [4]. For the initiation of callus culture, the following factors are important-: the origin of explants used for the establishment of callus culture, the cellular/tissue differentiation status, external plant growth regulators, culture media and culture conditions [46].…”
Section: Organogenesismentioning
confidence: 99%